Diseño y simulación de un banco hidráulico didáctico para la determinación de perdidas de energía por fricción del agua en tubería pvc y acero inoxidable (2020)
Learning in a didactic way through laboratory practices is essential in technical and professional training. Currently, the Laboratory of Thermo Fluids of the university Antonio Nariño Headquarters south does not have an infrastructure that allows active learning on issues of energy loss due to fluid friction. On the other hand, it is necessary to carry out the simulation of a didactic tool with the possibility of analyzing the behavior of the variables of a turbulent fluid on two different types of materials, in this case PVC and stainless steel to carry out the comparison of the effect of the roughness of each material. The main objective is to achieve effective learning about major energy losses in pipes with different diameters and roughness, minor losses in accessories such as fittings and valves. The design and simulation process involves initially developing theoretical calculations that are the support for each type of test. A a environment simulación was developed in Java which allows analyzing the energy losses in the pipeline, making modifications to various parameters that intervene in this analysis. A physical prototype is made for data collection and comparing with the data provided by the simulator's graphical interface. Presentation documents were prepared as laboratory guides and technical information from the bank. The limitation that is placed on the algorithm is that during the interface the analysis of a fluid is performed, which in this case would be water, making some variations such as temperature. The implementation of the simulator was realistically based, giving an environment of quality, efficiency and flexibility in operation for future users.